The relationship between digitalization and servitization : the role of servitization in capturing the financial potential of digitalization - Kohtamäki, Marko; Parida, Vinit; Patel, Pankaj C.; Gebauerd, Heiko (Elsevier, 2020)
The present study investigates the effect of the interaction between digitalization and servitization on the financial performance of manufacturing companies. We challenge the simple linear assumption between digitalization and financial performance with a sample of 131 manufacturing firms and hypothesize a nonlinear U-shaped interaction effect between digitalization and servitization on financial performance. From low to moderate levels of digitalization, the interaction effect between digitalization and high servitization on company financial performance is negative and significant. From moderate to high levels of digitalization, the interplay between digitalization and high servitization becomes positive and significant, improving companies’ financial performance. The results demonstrate the need for an effective interplay between digitalization and servitization, the digital servitization. Without this interplay, a manufacturing company may face the paradox of digitalization. For managers of manufacturing companies, the study provides insights into the complex relationship between digitalization and financial performance, emphasizing the value of servitization in driving financial performance from digitalization. Thus, the study demonstrates how manufacturing companies can become data-driven by advancing servitization.
Keywords: digital servitization business model; product-service systems (PSS); smart manufacturing (Industry 4.0); digitalization capabilities; Internet of Things (IoT); customer relationship management (CRM); fi=Johtaminen ja organisaatiot|en=Management and Organization|